Transferring science-based technologies to industry: Does nanotechnology make a difference? - Christopher Plamberg; Mika Pajarinen; Tuomo Nikulainen (The Research Institute of the Finnish Economy (ETLA), 2007)
Nanotechnology has been touted as a general purpose technology (GPT) and engine of growth for the 21th century, following in the footsteps of ICT. Nanotechnology is still in an early phase of development, it is scientist driven and thus largely exogenous to the economy at present. In Finland the interest towards nanotechnology is also growing. This is visible especially through relatively large public R&D expenditures and numbers of scientific publications. A key question for the further development of nanotechnology towards commercialization in Finland, as well as for most other countries active in the field, is the degree to which channels for technology transfer from public research to firms can be established and supported further. This paper uses a new and extensive survey data covering individual Finnish researchers (and inventors) active in the field to assess whether nanotechnology brings forth new issues of policy relevance in the various dimensions of technology transfer. The results offer new insights into the definition of nanotechnology. Clear differences are also observed in the agents, modes, application and commercialization paths between researchers by the intensity at which they are engaged in nanotechnology. However, the challenges appear to be similar to those related to the transfer of science-based technologies generally. The paper also reports basic frequencies across the survey data as a whole.
Keywords: O31; O32; O38; 330; nanotechnology; Finland; technology transfer; survey data; Nanotechnologie; Technologietransfer; Innovationsdiffusion; Finnland